A review of the pathogenesis of mitochondria in breast cancer and progress of targeting mitochondria for breast cancer treatment - Aoling Huang; Haochen Xue; Ting Xie; Lingyan Xiang; Zhengzhuo Chen; Aolong Ma; Honglin Yan; Jingping Yuan (Journal of Translational Medicine)
Abstract With breast cancer being the most common tumor among women in the world today, it is also the leading cause of cancer-related deaths. Standard treatments include chemotherapy, surgery, endocrine therapy, and targeted therapy. However, the heterogeneity, drug resistance, and poor prognosis of breast cancer highlight an urgent need for further exploration of its underlying mechanisms. Mitochondria, highly dynamic intracellular organelles, play a pivotal role in maintaining cellular energy metabolism. Altered mitochondrial function plays a critical role in various diseases, and recent studies have elucidated its pathophysiological mechanisms in breast carcinogenesis. This review explores the role of mitochondrial dysfunction in breast cancer pathogenesis and assesses potential mitochondria-targeted therapies.